Comparison of the Effects of Lidocaine Versus Magnesium Infusion on Quality of Recovery After Nasal Bone Fracture Surgery - Eun Kyung Choi; Jongyoon Baek; Kyu Jin Chung (Medicina)
Background and Objectives: Postoperative recovery from general anesthesia is a multidimensional process, and patient-centered outcome assessment should be considered an important indicator of recovery quality. This study compared the effectiveness of intraoperative lidocaine and magnesium on postoperative recovery in nasal bone fracture surgery, using the quality of recovery-40 questionnaire (QoR-40) to assess recovery quality and pain intensity. Materials and Methods: A total of 74 patients scheduled for elective closed reduction surgery for isolated nasal bone fracture were assigned to the intraoperative infusions of lidocaine or magnesium. Immediately after anesthetic induction, 1.5 mg/kg lidocaine or 20 mg/kg magnesium was administered over 10 min, followed by a continuous infusion of 2 mg/kg/h lidocaine or 20 mg/kg/h magnesium until the end of the surgery. The primary outcome variable was the QoR-40 survey on postoperative day 1. The secondary outcome variables included postoperative pain intensity, sedation score, the incidence of postoperative nausea and vomiting, and other side effects. Results: The global QoR-40 score at postoperatively 24 h was comparable between the intraoperative lidocaine and magnesium groups. Postoperative pain 30 min after surgery was significantly lower in the lidocaine group than in the magnesium group (p = 0.01), along with lower rescue analgesic consumption (p = 0.003), but pain intensity was not different at other time points (2, 6, and 24 h). The incidence of nausea and vomiting and the sedation score in the post-anesthetic care unit were not significantly different between the two groups. Conclusions: Intraoperative lidocaine and magnesium had no difference in the scores of postoperative QoR-40, but lidocaine was associated with lower postoperative pain scores and analgesic requirement in comparison to magnesium in the closed reduction of nasal bone fractures.